Methanol Steam Reforming over ZnO/ZnZrOx: Performance Enhanced with a Cooperative Effect. Issue 1 (15th November 2021) - Chen, Xuelian; Wang, Jijie; Han, Zhe; Li, Chengbin; Tang, Chizhou; Zhao, Dongyuan; Yang, Qihua; Li, Can
Abstract: The steam reforming of methanol (SRM) provides an efficient approach for the H2 production, but current SRM catalysts suffer from low activity, selectivity and stability. Herein, we report that ZnO nanoparticles (NPs) supported on ZnZrOx solid solution have excellent catalytic properties for SRM. The systematic studies suggest that ZnO/ZnZrOx catalysts with smaller ZnO domain (1–2 nm) are more selective and active than those with larger ZnO NPs. The existence of cooperative effect between the ZnO NPs (for methanol activation) and ZnZrOx solid solution (for water activation) was verified by the control experiment with ZnO/Al2 O3 and ZnZrOx as catalysts. In situ DRIFTS of SRM and TPSR/MS studies suggest that the reaction undergoes through formates pathway over ZnO/ZnZrOx, where ZnO NPs and ZnZrOx work in a cooperative mode to favor the SRM reaction and suppress the side reactions. The optimized ZnO/ZnZrOx catalyst affords 99.7 % methanol conversion with CO selectivity as low as 2.4 % for single‐pass in a fixed bed reactor. Abstract : Enhancing performance : ZnO/ZnZrOx catalysts obtained by wet‐impregnation method act as efficient methanol steam reforming catalysts. The cooperative effect between ZnO NPs domain and ZnZrOx solid solution enhances the activity and suppresses the CO formation.